CHECKING THE ACCURACY OF LABORATORY TESTS - Otto Dvořák; František Wald (Civil Engineering Journal, 2019)
In fire engineering, the quality of results of crucial test methods is key for validation of advanced numerical models. Therefore, it is important that the correct functioning of the test equipment and test procedures is achieved. This contribution is an assessment of the accuracy respectively the precision of the test methods based on the knowledge of the repeatability r and the reproducibility R determined by the round robin test (inter laboratory comparison) with reference testing materials.